Children's Environmental Identity Development with Descriptive Phenomenology Approach - Ambar Sri Lestari; Jumarddin La Fua; Imelda Wahyuni (Jurnal Pendidikan Indonesia, 2024)
Students often have low environmental awareness. This can be seen from daily behavior that does not pay attention to the importance of maintaining and caring for the environment. One way to improve students' ability to develop environmental identity is through Environmental Education (PLH). This research aims to explore the development of environmental identity of students in grades four to six of Champion Elementary School in the city of Bandung through outdoor learning experiences. The type of research used is qualitative with a phenomenological approach. Data were collected through semi-structured interviews with 12 participating students, using open-ended questions and analyzed by Colaizzi's descriptive phenomenological methods. This research aims to explore the development of environmental identity of students in grades four to six of Champion Elementary School in the city of Bandung through outdoor learning experiences. The type of research used is qualitative with a phenomenological approach. Data were collected through semi-structured interviews with 12 participating students, using open-ended questions and analyzed by Colaizzi's descriptive phenomenological methods. The findings of this study reveal that children develop their environmental identity through outdoor learning experiences that include four aspects: Environmental Love Movement, Clean and Neat Champion (Jurasik), Waste Management, and Eco-Friendly Activities. These aspects are integrated into the overall pro-environment attitude of students. This research has implications for increasing students' awareness of attitudes and literacy towards the environment.